If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -6(3x + -4) = 11 Reorder the terms: 6 + -6(-4 + 3x) = 11 6 + (-4 * -6 + 3x * -6) = 11 6 + (24 + -18x) = 11 Combine like terms: 6 + 24 = 30 30 + -18x = 11 Solving 30 + -18x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + -18x = 11 + -30 Combine like terms: 30 + -30 = 0 0 + -18x = 11 + -30 -18x = 11 + -30 Combine like terms: 11 + -30 = -19 -18x = -19 Divide each side by '-18'. x = 1.055555556 Simplifying x = 1.055555556
| 7m+p=q | | 2.5n=21 | | a=(3.14)(26) | | -40=7+p | | 35=7(7m+7) | | 5x+12=3x-18+3x | | -3=(v-7)-6v | | -13+x=x+11 | | 16m^2-19r^3= | | 10-3x+12=10 | | 9q=26.28 | | 2y+12=2(2y-3) | | 2.8/1.32=x/38.75 | | x-72=5.8 | | 3.5x+56.4=35.8-6.8x | | f(x+7)=x^2-3x+8 | | 1x+4=1x+2 | | 0.5n=0.85 | | 2y-61=y+10 | | 2x-3-5x=14+5x-1 | | 16m^2-19r^2= | | 1x+4=2+3 | | 7-2x=51 | | 6x+2-3=17 | | 39+6x=45 | | 5x+(-x)-5=23 | | 24m^9+48m^6+30m^3= | | x+(-6)=7 | | x+3x+x+3x=48 | | 1k+1v+1f=1x+1v | | -1+4x=-3x+35 | | x/-10=2 |